VARIASI BAHASA DAN GENDER DALAM ACARA SEMPROD DAN PODSKUY PADA YOUTUBE KUY ENTERTAINMENT (KAJIAN SOSIOLINGUISTIK) - Fifiony Mirza Ain’ni; Dede Fatinova (Prosiding Seminar Nasional Sasindo, 2022)
This study examines how language relates to gender diversity in YouTube speech. The purpose of this study is to describe language and gender variations in the Kuy entertainment youtube account on the Semprod and Podskuy events. This research is a qualitative descriptive research. The research data was collected using the listening method with the basic listening technique and the advanced listening technique, free to engage in conversation. The data in this study are excerpts of conversational dialogues on YouTube Kuy Entertainment. The data in this study were analyzed using Coates (2016) theory of male language characteristics and Lakoff's (2009) female language theory. Based on the results of the analysis, 45 data were found covering the topics of stereotype masculine, men only, great attention on detail, elaborated of taboo words, empty adjectives, intensifiers, hedges, superpolite forms, avoidance of swear words, and empathic stress.Kata Kunci/Keywords: : sociolinguistics, language and gender, language function